2020
DOI: 10.3390/ijerph17124536
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Stress Intensity and Coping Strategy and the Quality of Life of Nursing Students in Poland, Spain and Slovakia

Abstract: Background: This study aimed to determine the relationship between stress intensity and coping strategies and the quality of life and health among nursing students in Poland, Spain and Slovakia. Methods: The study was performed on a group of 1002 nursing students from three European countries. A diagnostic survey was used as a research method and the data collection was based on the Perceived Stress Scale PSS-10, Mini-COPE Coping Inventory-and the WHOQoL-Bref questionnaire. Results: The average age of all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 49 publications
(51 reference statements)
6
49
1
3
Order By: Relevance
“…Similar results were measured in Russian students, who reported low, moderate and high stress in prevalence of 26.0%, 69.1% and 4.9% [43]. On the other hand, Kupcewicz and his research team [45] revealed that 41.3% and 45.4% of Slovak nursing students suffered from moderate and high stress, simultaneously, 49.8% of Polish nursing students and 43.8% of Spanish nursing students reported high levels of the PSS stress score. Also, Orosova et al [41] identified 24.7% of Slovak students with a higher level of stress using the 4-item Cohen's PSS tool.…”
Section: Prevalence and Levels Of Stress Depression And Alcohol Usesupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results were measured in Russian students, who reported low, moderate and high stress in prevalence of 26.0%, 69.1% and 4.9% [43]. On the other hand, Kupcewicz and his research team [45] revealed that 41.3% and 45.4% of Slovak nursing students suffered from moderate and high stress, simultaneously, 49.8% of Polish nursing students and 43.8% of Spanish nursing students reported high levels of the PSS stress score. Also, Orosova et al [41] identified 24.7% of Slovak students with a higher level of stress using the 4-item Cohen's PSS tool.…”
Section: Prevalence and Levels Of Stress Depression And Alcohol Usesupporting
confidence: 77%
“…Polish medical students obtained a mean PSS score of 22.78 [44]. In another international study of nursing students, Slovak, Polish and Spanish students reported similar mean values for the 10-item PSS score, which indicated moderate stress (Slovak Republic = 18.66, Poland = 18.60, Spain = 18.55) [45]. In this context, several studies have revealed that medical students are at higher risk of stress compared to non-medical students [46,47].…”
Section: Perceived Stressmentioning
confidence: 88%
“…Students from Spain obtained lower average values (26.03) of global self-esteem than nursing students from Poland and Slovakia (29.69 vs 29.10). Comparing the mean values obtained in own research with the mean results (30.85) obtained for the data collected in 53 countries by other researchers, it can be concluded that, as in most countries, most the examined nursing students obtained results higher than the arithmetic midpoint of the scale [ 22 ].…”
Section: Discussionmentioning
confidence: 74%
“…The presented research results are part of a larger international research project [ 22 ]. The research meets the criteria for a cross-sectional study [ 23 ], and the project received approval (No.…”
Section: Methodsmentioning
confidence: 99%
“…1 Over the centuries, the concept of quality of life evolved and became an ambiguous and multidimensional construct, reflecting numerous aspects of human life and activities. 2,3 In the literature, the concept of quality of life is defined in several ways. 1 The World Health Organization (WHO) defines quality of life as the subjective assessment by an individual of their life situation in relation to the culture in which they live, and their system of values, goals, expectations and interests.…”
Section: Introductionmentioning
confidence: 99%